CONTRIBUTING FACTORS LINKED TO THE INCREASED RISK OF MULTI-DRUG- RESISTANT TUBERCULOSIS IN PAKISTAN, META-ANALYSIS. : J Peop Univ Med Health Sci. 2025:15(2), 245-253.http://doi.org/10.46536/jpumhs/2025/15.02.647 - Ghulam Mustafa Jamali1, Safdar Ali Jamali2, Mujahid Ali Chandio3, Abdul Ghani Rahimoon4, Kuldeep Kumar5, Mahwish Memon6, Areeba Batool7. (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: One of the most important public health issues related to tuberculosis (TB) is the growing problem of multidrug-resistant TB (MDR-TB), especially in high-burden countries like Pakistan. MDR-TB is defined as tuberculosis caused by strains which are resistant to at least two of the most used first-line treatments for TB. There are many factors supporting the emergence and spread of MDR-TB in Pakistan including socio-economic status, healthcare infrastructure, treatment compliance levels, and even population movement. OBJECTIVE: This aim of this meta-analysis is looking into demographic details along with previous treatment history, somatic illnesses, surrounding environment, and other relevant factors to assess their contribution towards the development and progression of MDR-TB in Pakistan. METHODS: We reviewed literature published from 2000 to 2024. The studies included in this meta-analysis featured both cross-sectional and cohort designs of varying sample sizes. Multiple databases related to medicine and public health were searched for relevant articles. Information including age, sex, education, job title, previous tuberculosis management, other existing health illnesses, and their housing conditions were gathered. RESULTS: The most significant risk factors are a history of treatment for TB, low educational level, poor compliance with treatment, lack of employment, and close contact with MDR-TB patients. The most affected age group is 20 to 40 years, with an almost equal predominance of males. The most common reported comorbidities are diabetes, CKD, and HIV, that also raise the risk of developing MDR-TB. Moreover, crowded living arrangements and restricted healthcare access were identified as prominent drivers of the problem. CONCLUSION: This meta-analysis calls for complete strategies to address MDR-TB in Pakistan. It is essential to counteract socio-economic disparities, enhance TB medication adherence, and enhance household screening and prevention measures to manage the transmission of MDR-TB efficiently. Public health activities should target high-risk populations, especially those with a past history of TB infection or comorbid conditions.